Ultra-sensitive and high-throughput CRISPR-p owered COVID-19 diagnosis - Huang, Zhen; Tian, Di; Liu, Yang; Lin, Zhen; Lyon, Christopher J.; Lai, Weihua; Fusco, Dahlene; Drouin, Arnaud; Yin, Xiaoming; Hu, Tony; Ning, Bo (Biosensors & bioelectronics, 2020)
Recent research suggests that SARS-CoV-2-infected individuals can be highly infectious while asymptomatic or pre-symptomatic, and that an infected person may infect 5.6 other individuals on average. This situation highlights the need for rapid, sensitive SARS-CoV-2 diagnostic assays capable of high-throughput operation that can preferably utilize existing equipment to facilitate broad, large-scale screening efforts. We have developed a CRISPR-based assay that can meet all these criteria. This assay utilizes a custom CRISPR Cas12a/gRNA complex and a fluorescent probe to detect target amplicons produced by standard RT-PCR or isothermal recombinase polymerase amplification (RPA), to allow sensitive detection at sites not equipped with real-time PCR systems required for qPCR diagnostics. We found this approach allowed sensitive and robust detection of SARS-CoV-2 positive samples, with a sample-to-answer time of ~50 min, and a limit of detection of 2 copies per sample. CRISPR assay diagnostic results obtained nasal swab samples of individuals with suspected COVID-19 cases were comparable to paired results from a CDC-approved quantitative RT-PCR (RT-qPCR) assay performed in a state testing lab, and superior to those produced by same assay in a clinical lab, where the RT-qPCR assay exhibited multiple invalid or inconclusive results. Our assay also demonstrated greater analytical sensitivity and more robust diagnostic performance than other recently reported CRISPR-based assays. Based on these findings, we believe that a CRISPR-based fluorescent application has potential to improve current COVID-19 screening efforts. •Integrated CRISPR for COVID-19 clinical diagnosis.•Rapidly identify SARS-CoV-2-specific RNA signatures at an ultra-low concentration.•Detection environment friendly and compatible for high throughput COVID-19 screening in hospital.•Successful development and validation with swab samples from patients.•Improve diagnosis of individuals with suspected COVID-19 infections.